Intermediate Financial Management / Sixth Edition - Brigham Eugene F; Daves Phillip R; Gapenski Louis C (The Dryden Press, 1999)
Preface, Fundamental Concepts, An Overview of Financial Management, Basic Financial Tools: A Review, Analysis of Financial Statements, Extensions, Valuing the Firm: The Cash Flow Model, Strategic Investment Decisions,Determing the Cost of Capital, Capital Budgeting Decision Criteria, Cash Flow Estimation, Risk Analysis and Real Options, Extensions, Strategic Financing Decisions, Long-Term Financial Planning, Capital Structure Decisions, Extensions, Dividend Policy, Tactical Financing Decisions, Investment Banking and Financial Restructuring, Lease Financing, Extensions, Hybrid Financing, Working Capital Management, Current Asset Management, Short-Term Financing, Extensions, Special Topics, Derivatives and Risk Management, Bankruptcy and Reorganization and Liquidation, Extensions, Basic Tools: A Review, Risk and Return, Bond and Stock Valuation, Extensions, Appendixes, Index.
Preface, Fundamental Concepts, An Overview of Financial Management, Basic Financial Tools: A Review, Analysis of Financial Statements, Extensions, Valuing the Firm: The Cash Flow Model, Strategic Investment Decisions,Determing the Cost of Capital, Capital Budgeting Decision Criteria, Cash Flow Estimation, Risk Analysis and Real Options, Extensions, Strategic Financing Decisions, Long-Term Financial Planning, Capital Structure Decisions, Extensions, Dividend Policy, Tactical Financing Decisions, Investment Banking and Financial Restructuring, Lease Financing, Extensions, Hybrid Financing, Working Capital Management, Current Asset Management, Short-Term Financing, Extensions, Special Topics, Derivatives and Risk Management, Bankruptcy and Reorganization and Liquidation, Extensions, Basic Tools: A Review, Risk and Return, Bond and Stock Valuation, Extensions, Appendixes, Index.